Psychological Impact in Health Care Workers during the Outbreak of COVID-19: A Literature Review - Anita Setyawati; Etika Emaliyawati; Clarabelle Puspitadewi Kuncoro; Rini Lestari; Syahrizal Syahrizal; Finka Laili Nur Adzillah; Aliffa Azwadina (Universitas Padjadjaran, 2021)
The COVID-19 outbreak is a worrying problem worldwide and health care workers have a big responsibility in responding to this condition. The increase in the number of COVID-19 patients which causes an increase in the workload of health care workers, scarcity of personal protective equipment, and stresses during work, can lead to psychological instability in health care workers.The study aims to identify the psychological conditions experienced by health care workers during the COVID-19 pandemic.The search for articles was carried out on the online digital database, Science Direct, and PubMed with the keywords 'COVID-19', 'psychological or psychology or mental health', 'nurse'. Then the articles are selected according to the inclusion criteria, namely the results of research in 2019-2020, full text, published in English, and articles discussing the psychological and mental conditions of health care workers who are assigned to the COVID-19 pandemic. In the end, 7 articles were analyzed in this literature review.In carrying out their duties during the COVID-19 pandemic, health care workers are prone to experiencing psychological disorders such as anxiety and insomnia. High workload, lack of personal protective equipment, lack of knowledge about the prevention and transmission of COVID-19, and pressures during work, are the main triggers for psychological problems experienced by health care workers. Therefore, coping strategies that come from internal and external need to be obtained by health care workers to reduce the psychological disturbance they experience.